HISTOPATHOLOGICAL EVALUATION OF ENROFLOXACIN INDUCED OXIDATIVE STRESS AND ITS AMELIORATION WITH ANTIOXIDANTS - A. Elamaran; S. Vairamuthu; S. Ramesh; P. Hariharan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
In this research work, an attempt has been made to study the histopathological changes of oxidative stress caused by enrofloxacin at therapeutic doses and its restoration by alpha-lipoic acid and its comparison with conventional antioxidant vitamin E in tissue homogenates like liver, kidney and heart of broilers. Enrofloxacin was administered to the broiler birds orally at the dose of 10 mg/kg body weight once daily from day 38 to day 42. Histopathological examination revealed marked congestion and bile duct hyperplasia of liver, degeneration and swelling of tubular epithelial cells in kidney. Interestingly, there was no appreciable lesion in the heart. Treatment with either alpha-lipoic acid (100 mg/kg body weight) or vitamin E (100 mg/kg body weight) showed moderate restoration of changes observed in liver and kidney compared to normal control birds. Co-treatment of alpha-lipoic acid (100 mg/kg body weight) and vitamin E (100 mg/kg body weight) showed restoration of liver and kidney architecture towards normal.